Spirituality in the administration and management of social welfare programs - Jimenez, Caroline G (2007)
This thesis discusses a qualitative study that explored both the implementers' and the clienteles' viewpoints regarding the reasons and implications of integrating spirituality in terms of commitment, motivations, core values and professional values of the administrations and implementers of Tahanan Mapagkalinga ni Madre Rita (TMMR), Inc. and of Mother Rita Community Center (MRCC), Inc. as practices in social work administration towards effective delivery of social services...
"March 2007."
Thesis (M. Social Work)--University of the Philippines Diliman.
Keywords: Social work administration -- Philippines -- Religious aspects; Church work -- Religious aspects